A Pilot Study on the Relationship between Cardiovascular Health, Musculoskeletal Health, Physical Fitness and Occupational Performance in Firefighters - Jaron Ras; Denise L. Smith; Elpidoforos S. Soteriades; Andre P. Kengne; Lloyd Leach (MDPI AG, 2022)
Firefighters' face life threatening situations and are frequently exposed to numerous physical, chemical, biological, ergonomic and psychosocial hazards. The purpose of this pilot study was to investigate the feasibility of conducting a large-scale study on cardiovascular and musculoskeletal health, physical fitness and occupational performance of firefighters. We conducted a cross-sectional pilot study by recruiting 36 firefighters. A researcher-generated questionnaire and physical measures were used to collect data on sociodemographic characteristics, cardiovascular and musculoskeletal health, physical fitness and occupational performance using a physical ability test (PAT). We documented a high equipment and intra-assessor reliability (r > 0.9). The potential logistic and/or administrative obstacles in the context of a larger study were discerned. Data were successfully retrieved using available equipment and survey instruments. Hypertension (30.6%) dyslipidaemia (33.3%), obesity (36.1%) and physical inactivity (66.7%) were the most prevalent cardiovascular disease risk factors. A significant difference between genders in total PAT completion time was also seen (p < 0.001). Cardiorespiratory fitness, lean body mass, grip strength and leg strength were significantly associated with occupational performance (p < 0.001). The pilot study supports the larger study feasibility and verified equipment and assessors' reliability for research. Cardiovascular health, musculoskeletal health and physical fitness may be related to PAT performance.